PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PIZZA HUT PEMUDA JAKARTA - Muhamad Ripki; M. Kausar Maulana (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
The purpose of the research in the know the leadership style and motivation that can improve the employee performance so that the research will take the title: Influence of leadership style and employee performance motivation at Pizza Hut Pemuda Jakarta. The data analysis methods used are statistical tests using multiple linear regression analysis techniques and partial linier regression. The test results of the study concluded that there was a significant influence between the leadership force on employee performance, and there was a significant influence between the motivation to employee performance. The result of leadership style is positively influential towards employee performance, while the result of motivation also has an effect on employee performance.